Beyond the Green-Zone Stereotype: Mapping Inclusivity, Religious Moderation, and Radicalization Risk in Bali’s Public Schools - Emawati, Emawati; Muthi'ah, Anisatun; Zuhriyah, Lailatuzz; Ahsan Thofhani, Lalu Nauval; Usman, Rachma Fadhila (Universitas Islam Negeri Ar-Raniry, 2026)
Radicalism in educational settings is a strategic issue that demands serious attention, especially amid the growing influence of religious ideologies that infiltrate through digital spaces and school social interactions. This study aims to map the levels of inclusiveness, religious moderation, tolerance, and national commitment in public schools in Denpasar City to understand their potential, strengths, and vulnerabilities in building Zero Radicalism Schools. This issue is vital because Bali is generally considered a region with a strong culture of tolerance, but this assumption may mask latent vulnerabilities that are not immediately apparent. The study employs a convergent mixed-methods design, combining quantitative surveys, interviews, observations, and document analysis across four public schools in Denpasar. Survey results indicate high levels of inclusiveness and religious moderation across all schools, while qualitative data highlight teachers as key actors in fostering a harmonious religious climate. Nevertheless, quantitative indicators related to anti-violence culture and interfaith literacy show fluctuating patterns, a finding further explained by qualitative evidence of uneven program implementation. These integrated findings suggest that Denpasar’s schools are well positioned to develop a Zero Radicalism School model, although improvements in digital literacy, peace education, and monitoring systems remain necessary.